Pengaruh Kompetensi dan Motivasi Kerjaterhadap Kinerja Pegawai di Dinas Kearsipan dan Perpustakaan Kota Banjar - Marlina Marlina; Enas Enas; Irma Bastaman (Jurnal Manajemen Bisnis Digital Terkini, 2024)
Human resources are very valuable assets and are a major investment that can determine the progress of an organization. Human resources who have knowledge, skills and attitudes that are in accordance with the needs of the organization will encourage creativity and new innovations so that they become a source of unique competitive advantage that is difficult to imitate. Thus, human resources as an asset in an organization must be managed effectively so that they are useful and effective in realizing organizational goals. Employee performance can be used as a benchmark to assess the progress of an organization. Performance measures can be seen from the number and quality of certain aspects according to the standards set by the organization or company, the form can be tangible (the measuring instrument or standard can be determined) or intangible (the measuring instrument or standard cannot be determined), depending on the form and process of implementing the work. This study aims to determine the level of work competence and work motivation as an effort to improve the performance of employees of the Archives and Library Service of Banjar City. This study uses a descriptive survey method, namely research that seeks to collect data, critically analyze the data and conclude it based on facts during the research period. The population in this study were employees of the Archives and Library Service of Banjar City, both civil servants and non-civil servants. Data processing used SPSS version 20. The results of the study were obtained from the results of testing with multiple linear regression tests showing that competence had an effect of 48.3%, and work motivation had an effect of 44.5% on performance partially, overall both variables had an effect of 78.9% and the remaining 21.1% was influenced by other factors.